Diasporas and Economic Development: A Review of the Evidence and Policy - Dany Bahar (Center for Economic Studies and ifo Institute (CESifo), 2020)
The paper reviews recent literature on the economics of migration and diasporas, focusing on economic gains and opportunities that these diasporas could represent for home countries. In addition, the paper discusses policies aimed at leveraging this "diaspora capital".
Keywords: O33; F14; F22; 330; migration; diaspora; trade; FDI; remittances; knowledge